Characterization of the Chemical Composition Distribution of Ethylene/1‐Alkene Copolymers with HPLC and CRYSTAF—Comparison of Results. Issue 7 (4th February 2015) - Chitta, Rajesh; Macko, Tibor; Brüll, Robert; Boisson, Christophe; Cossoul, Emilie; Boyron, Olivier
<x xml:space="preserve">Abstract</x> A series of copolymers of ethylene with propene, 1‐hexene, 1‐octene, and 1‐octadecene is characterized by size‐exclusion chromatography (SEC), nuclear magnetic resonance spectroscopy (NMR), crystallization analysis fractionation (CRYSTAF), and high‐temperature interactive liquid chromatography. Four different solvent pairs are used as the mobile phase, while porous graphite is used as the column packing. The elution volumes of the polymer samples do not correlate with their average molar mass (SEC); however, they correlate with the average chemical composition (NMR). High performance liquid chromatography (HPLC) enables separation of the copolymers over the full range of their composition and independent of their crystallinity. Dependence between the elution volume and the average chemical composition distribution (CCD) of the copolymer is linear and it is a function of the length of branches as well as the type of the mobile phase. The CCDs of copolymers derived from HPLC profiles are similar to, yet broader than the CCDs obtained with CRYSTAF. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>